MRI Quantification of Left Atrial Circumferential Strain in Mitral Regurgitation: A Feasibility and Reproducibility Study - Sreedhar, Siva P.; Gupta, Aakash; Chitiboi, Teodora; Pradella, Maurice; Elbaz, Mohammed S.M. (Journal of magnetic resonance imaging, 2024)
Background MRI‐derived left atrial (LA) longitudinal strain has been shown to be a marker for mitral regurgitation, but the utility of LA circumferential strain remains unclear. Purpose To assess feasibility and reproducibility of LA circumferential strain, identify changes in mitral regurgitation patients compared to healthy volunteers, and determine strain's association with mitral regurgitation severity and cardiac function. Study Type Retrospective. Population 52 mitral regurgitation patients, 12 healthy volunteers. Field Strength/Sequence Steady‐state free precession cine and 2D phase contrast sequences at 1.5T. Assessment Peak LA circumferential strain was computed in each of three short‐axis slices (superior, mid, and inferior) and longitudinal strain computed from long‐axis slices using MRI feature‐tracking software. Strain test–retest reproducibility was determined from two repeat studies in healthy volunteers. Statistical Tests LA circumferential strain test–retest reproducibility was assessed by intra‐class correlation coefficient (ICC). Strain was compared between cohorts using Student's t‐test or Mann–Whitney U. Mitral regurgitation severity association with strain and LV function was assessed using Spearman correlation and multivariable regression. Significance was defined as P < 0.05. Results LA circumferential strain assessment was feasible in all subjects with moderate reproducibility in the superior (ICC = 0.74), mid LA (ICC = 0.71), and inferior LA (ICC = 0.63). In mitral regurgitation patients, LA circumferential strain was significantly lower in the superior (11.86% [6.5%,19.2%] vs. 18.73% ± 6.7%) and mid LA slices (18.41% ± 9.5% vs. 28.7% ± 10.4%) compared to healthy volunteers. Mitral regurgitation severity significantly associated with mid LA circumferential strain (β = −0.03) and LAV significantly associated with superior LA circumferential strain (β = −2.09), both independent of LA longitudinal strain and CO. Data Conclusion LA circumferential strain assessment is feasible with moderate reproducibility. Compared to healthy volunteers, patients had significantly lower LA circumferential strain. Mitral regurgitation severity and LAV were significantly associated with LA circumferential strain independent of LA longitudinal strain. Evidence Level 3 Technical Efficacy Stage 2